2021
DOI: 10.4103/jmh.jmh_86_21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and safety of rheum rhaponticum root extract (err 731) for menopausal symptoms in perimenopausal indian women: An interim analysis

Abstract: Background: Hormonal therapy for menopause has been found to be the most efficacious treatment, but it may be associated with adverse effects in some of the women. Rheum rhaponticum root extract (”ERr 731”), which is available worldwide, is a natural, reliable, effective, and well-tolerated remedy for women in perimenopausal women with menopausal symptoms (MSs), but there is no Indian study demonstrating its efficacy, safety, and tolerability till date. Objective: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…147 Another open-label, single-arm study in Indian perimenopausal women over 12 weeks reported improved menopause symptoms. 148 Given the extremely low retention rate in clinical trials and the open-label study design in one study, the conclusions are limited. (Level II; not recommended)…”
Section: Rhubarbmentioning
confidence: 99%
“…147 Another open-label, single-arm study in Indian perimenopausal women over 12 weeks reported improved menopause symptoms. 148 Given the extremely low retention rate in clinical trials and the open-label study design in one study, the conclusions are limited. (Level II; not recommended)…”
Section: Rhubarbmentioning
confidence: 99%
“…The hormonal changes during menopause result in various physical, psychological, and emotional changes that manifest as different symptoms, including hot flashes, night sweats, mood swings and irritability, vaginal dryness and discomfort during sexual intercourse, sleep disturbances, weight gain, slowed metabolism, joint pain, muscle pain and stiffness, memory and concentration problems, urinary incontinence, frequent urination, and loss of libido and sexual function [ 5 ] . Additionally, various studies have demonstrated that metabolic syndrome significantly increases the severity of menopause symptoms [ 1 ] .…”
Section: Introductionmentioning
confidence: 99%
“…1 ), which is believed to reduce the severity of climacteric symptoms [ 9 ] . ERr 731 ® is a standardized R. rhaponticum root extract that has been clinically evaluated for its potential use in the management of menopausal symptoms [ 5 ] . However, the literature lacks a dedicated systematic review and meta-analysis to evaluate the effectiveness of ERr 731 ® supplementation in reducing the severity of menopausal symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation